Sensors based on monochromatic interrogation of a localised surface plasmonresonance - Kealley, Cat; Arnold, M.; Porkovich, A.; Cortie, M. (Elsevier SA, 2010)
The localised surface plasmon resonance in gold nanoparticles can be used as the basis of a refractometric sensor. Usually, this is accomplished by monitoring a shift in wavelength of the resonance peak, a task which requires measurements over a range of wavelengths. Here we investigate a different scheme, in which interrogation of the sensor is carried out at a single wavelength. We have used numerical simulations to estimate the effect that the shape of gold nanoparticles would have on the performance on such sensors. A variety of geometries of gold nanoparticles were investigated, including nano-spheres, nano-rods, nano-triangles, and nano-bowties. The performance of a sensor that operates at a single wavelength is controlled by dT/dn, the change in transmittance T with refractive index n, determined at the interrogation wavelength. In turn, dT/dn depends upon the extinction cross-section of the nanoparticles at the chosen wavelength, and on the density of the nanoparticles in the light path. Contributions to the sensor efficiency also include the shift in wavelength of the plasmon resonance and, importantly, the peak sharpness. Of the particles examined, gold nano-rods will provide the most sensitive sensors by a large margin.